Investigation on the thermal performance of a multi-tube finned latent heat thermal storage pool. (5th January 2022) - Huang, Yongping; Song, Liping; Wu, Suchen; Liu, Xiangdong
Highlights: Innovative multi-tube finned latent heat thermal storage pool (LHTSP) is designed. Charing/discharging duration of innovative LHTSP shortens by up to 29.4% and 22.8%. Thermal performance is mainly determined by later charging/discharging stages. Vertical installation facilitates minimizing the heat charging duration. Inclination affects the heat charging process more than discharging process. Abstract: The major challenge of multi-energy complementary systems consists of improving the thermal efficiency for latent heat thermal storage pools (LHTSPs). To address this, a new multi-tube LHTSP with tree-shaped fins is designed herein. The enthalpy-porosity approach is employed to model the charging/discharging process in LHTSPs, focusing on the role of inclinations in melting/solidification heat transfer. Moreover, experimental validation is conducted to ensure numerical reliability. The results show that tree-shaped fins effectively improve thermal efficiency and temperature uniformity. Compared with traditional LHTSPs, the innovative LHTSP shortens the total melting/solidification time by up to 29.4% and 22.8%, respectively, and improves the temperature uniformity by 12.3%∼19.2%. The difference in the influence regime of natural convection during melting and solidification lies in its onset and duration. Moreover, the thermal performance of LHTSPs is mainly related to the later charging/discharging stage. The inclination significantly affects the thermal charging performance, while it has less influence on the discharging processes. Compared to the horizontal arrangements, the innovative vertical LHTSP has a 46.3% reduction in the melting duration. Interestingly, there is a transition point in the heat storage efficiency of horizontal and vertical LHTSPs, and the LHTSP arrangement with a higher efficiency differs before and after this point.